Diet management of older subjects with Oropharyngeal Dysphagia: The efficacy of ready-made texture-modified and fortified meals - Nikolina Jukic Peladic; Paolo Orlandoni; Laura Bartoloni; Giulia Giulioni; Claudia Venturini; Alessia Fumagalli (Clinical Nutrition Open Science)
Summary: Background: In-home prepared texture-modified diets are not efficient in preventing the consequences of Oropharyngeal Dysphagia (OD); malnutrition and aspiration pneumonia. Difficulties with their preparation and administration aggravate also the burden of caregivers. This study investigated whether the ready-made texture-modified meals, fortified with amino acids and Vitamin D, may guarantee safe and efficient management of meals in older subjects with OD and facilitate patient management. Methods: Patients who were assessed for dysphagia and nutritional status at the Clinical Nutrition Unit of Ancona and the Pneumology Unit of Casatenovo (LC) of the National Institute of Health and Science on Aging (IRCCS) INRCA and diagnosed with level 4 severity of OD according to IDDSI framework, were invited to use at lunch, for seven consecutive days, the ready-made fortified meals. Face-to-face and phone interviews were used to collect the socio-demographic data and testimonies of 30 out-hospital patients with OD and their formal and informal caregivers in order to assess the safety and liking of products. Simple descriptive statistics were used to summarize the results of the interviews. Results: Out of 493 tastings, only 20 (4%) were interrupted because of an minor adverse event. Ready-made meals, and sweet desserts in particular, were appreciated by subjects with OD; 95% of dishes were consumed entirely, thus ensuring the satisfaction of the protein-calorie needs of patients. Ready-made products positively affected caregiving (75%), especially because the food administration was less time-consuming (90%). Conclusions: Ready-made texture-modified fortified food seem promising in ensuring the improvement in patients' safety and easing the caregivers' tasks. The specific needs of patients with OD relative to diet consistency and protein-calorie needs should be defined by healthcare staff while the meeting between the needs of patients and the offer of ready-made products should be mediated by the mandatory use of a universal scale for the definition of diet texture.